2005
DOI: 10.1210/en.2005-0502
|View full text |Cite
|
Sign up to set email alerts
|

The Telomerase Activity of Adult Mouse Testis Resides in the Spermatogonial α6-Integrin-Positive Side Population Enriched in Germinal Stem Cells

Abstract: Testis is one of the organs with the most telomerase activity in the adult. This activity protects chromosomes from telomere attrition and ensures the transmission of full-length chromosomes to progeny. Little is known about telomerase activity during adult germ cell differentiation, however. We demonstrate here that the telomerase activity of adult mouse testis resides in the alpha6-integrin-positive Side Population containing spermatogonia and enriched in spermatogonial stem cells. The telomerase activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Previous studies attempting to localize telomerase expression within the germ cell lineage showed widely divergent results. A subset of the studies did find elevated expression in partially purified spermatogonia, which is consistent with our data (Ravindranath et al 1997;Kanatsu-Shinohara et al 2003;Riou et al 2005).…”
Section: The Tertsupporting
confidence: 91%
“…Previous studies attempting to localize telomerase expression within the germ cell lineage showed widely divergent results. A subset of the studies did find elevated expression in partially purified spermatogonia, which is consistent with our data (Ravindranath et al 1997;Kanatsu-Shinohara et al 2003;Riou et al 2005).…”
Section: The Tertsupporting
confidence: 91%
“…It is generally accepted that only few normal cell types such as male germ-line spermatocytes and around 90% of all cancers exhibit telomerase activity [164,165]. In adult mice, telomerase was detected in a positive α6-integrin subpopulation containing spermatogonia and enriched in spermatogonial stem cells [166]. …”
Section: Hallmarking Cancermentioning
confidence: 99%
“…Today, Hoechst 33342 excluding cells are commonly referred to as side population cells. Such cells can be found in a wide variety of tissues, and the side population strategy has been useful for isolating cells with high regenerative capacity from hematopoietic (3, 5, 6), airway (7), pituitary (8), small intestine (9), and testicular (10) tissues. However, given the wide array of biological functions that ABC transporters serve, and the fact that they are sometimes induced in transporter-negative cells by substrate exposure, the caveat must be given that MDR expression does not unequivocally identify stem cells and conversely, its absence does not rule out the self-renewing capacity most characteristic of stemness.…”
Section: Introductionmentioning
confidence: 99%